2008
DOI: 10.4321/s0004-06142008000600010
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma vesical linfoepitelioma-like: revisión de la literatura y aportación de un nuevo caso

Abstract: Resumen.-OBJETIVO: El carcinoma linfoepitelial o carcinoma linfoepitelioma-like es un raro tumor cuya histología recuerda a los linfoepiteliomas de la nasofaringe. Se ha descrito su presencia en múltiples localizaciones, pero en la vejiga tan sólo se han descrito 55 casos en la literatura. Presentamos un nuevo caso de carcinoma linfoepitelial vesical y hacemos una revisión de todos los publicados anteriormente, con la intención de definir sus características e intentar obtener una pauta terapéutica y pronóstic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This has been explicated by several authors who analyzed the lymphoid inflammatory component in LELCB by the importance of the inflammatory infiltrate and cytotoxic T-lymphocytes reflecting the strong immune response against the tumor cells and potentiating the effect of chemotherapy and radiotherapy [ 10 , 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has been explicated by several authors who analyzed the lymphoid inflammatory component in LELCB by the importance of the inflammatory infiltrate and cytotoxic T-lymphocytes reflecting the strong immune response against the tumor cells and potentiating the effect of chemotherapy and radiotherapy [ 10 , 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lymphoepithelial carcinoma of the nasopharynx is strongly associated with infection with the Epstein–Barr virus (EBV). However, no risk factor is known for LELC of the bladder [ 4 ]; the average age of patients was 65 years with a sex ratio (M:F) of 2:5 [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serrano et al [ 4 ] reported a recurrence-free survival in 87.5% of patients who had a pure form and stages T2 or T3. The prognosis of pure forms is linked to the importance of the inflammatory infiltrate and cytotoxic T lymphocytes for two reasons: early onset of symptoms causing patients to seek care, and strengthening the action of substances used in chemotherapy [ 4 ].…”
Section: Discussionmentioning
confidence: 99%